No ir e vir da balsa: o espaço de enunciação nas paisagens linguísticas da fronteira Porto Xavier/San Javier - Bratz, Mauricio Engroff (2023)
This study is part of the line of research “Language, Subject and History”, and addresses the situation of social and linguistic contact in the border area of Porto Xavier (BR) and San Javier (AR). Our objective is to understand the political and identity constitution of the frontier-missionary subject and his relationship with the language in this space of enunciation. We are also interested in demonstrating how the local social dynamics, that is, life on the frontier, makes possible an intercomprehension in the use of the Portuguese and Spanish languages, in particular, by the coming and going of the ferry, which transports people and products, moving the local economy and fostering diverse social interactions. The enunciation space constituted in the saying of these subjects, in the use of languages, including Portuguese in everyday social practices, is part of the constitution of the frontier identity. In this way, we intend to answer the following question: what are the political meanings in the use of Portuguese, Spanish and Portunhol by border speakers, in the Porto Xavier/San Javier border area? We will present, at first, a theoretical review of studies on languages in contact in border areas. Afterwards, we present our corpus, consisting of “Linguistic Landscapes” (PLs), represented by photographs of plaques of public and private spaces, which make up the space for the use of languages and signify them politically. We will carry out an interpretative analysis of these utterances, under the light of the concept of “Border Enunciation Space”, by Sturza (2006) and the principles of “Event Semantics”, by Guimarães (2002), using as an analytical category the movement of the notions of “nomination” and “designation”.